The Effect of Media Exposure, Family Closeness, and Knowledge about Sexually Transmitted Disease on Sexually Transmitted Disease Risk Behaviors in Senior High School Students - Oki Wihardiyanto; Flora Ramona Sigit Prakoeswa; Cita Rosita Sigit Prakoeswa (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2019)
Background: Sexually Transmitted Diseases (STDs) is one of the reproductive health problems that caused by unsafe sexual behavior. STDs can be caused by multiple factors, such as influenced by media exposure, family closeness, and the knowledge about STDs. The aim of this research is to evaluate the correlation between media exposure, family closeness, and knowledge about STDs on STDs risk behaviors in senior high school students. Methods: This study used cross sectional method, with 92 subjects of senior high school students, using family closeness questionnaire, media exposure questionnaire, and sexual knowledge and behavior questionnaire. The data were analyzed by Wilcoxon test and logistic regression test. Results: Based on the Wilcoxon test, the relation of media exposure, family closeness, and the knowledge about STDs with STDs risk behaviors obtained z scores 3.316 (p=0.001), -8.352 (p=0.000), -5.000 (p=0.000), respectively. The regression test showed a correlation value between media exposure, closeness, and the knowledge about STDs with STDs risk behavior of each 3.561 (p=0.040), 1.417 (p=0.011), 5.553 (p=0.037). Conclusion: There is a relationship between media exposure, family closeness, and the knowledge of STDs on STDs risk behaviors in senior high school students. Knowledge about STDs is the most influential factor in STDs risk behavior compared to media exposure and family closeness.